Are profit sharing rates of mudharabah account linked to interest rates? an investigation on Islamic banks in GCC countries - Rosylin Mohd. Yusof; Bahlous, Mejda; Tursunov, Hamza (Penerbit Universiti Kebangsaan Malaysia, 2015)
In principle, Islamic banking prohibits interest and advocates profit and loss sharing in its operations. Critics argue that in practice, Islamic banking is not totally interest free; but it focuses more on non-profit and loss sharing mechanisms instead. This study attempts to investigate the issue that the practices of Islamic banks are not totally free from interest and is arguably not totally in consonance with tenets of Sharia. It explores the relationship between the Profit rate offered by Islamic banks in GCC countries and the conventional interest rates. A long run analysis of the relationship between Profit Loss Sharing (PLS) rates and Conventional bank Interest rate (CBIR) for 18 Islamic Banks from the GCC countries conclude that there is no long run co-integration between CBIR and PLS rates. These results also seem to prevail even in the short run. The Variance Decompositions (VDC) analysis shows that except for Saudi Banks, there seems to be no significant link between the CBIR and the PLS. However for the case of Saudi banks, the link between PLS rate and interest rate is not strong enough to claim that Islamic Banking in practice is not interest free. Indeed, both the profit rates and the CBIR are linked to the real economy; and thus, this is reflected by the real rate of return in the economy. Therefore, we reject the claim that Islamic banks’ operations are not riba free.